Ultrasonography measurement of inferior vena cava diameter of blood donors as predictors for early blood loss in tertiary hospital northeastern, malaysia. - Shaik Farid, A W; Mohd Hashairi, F; Nik Hisamuddin, N A R; Chew, K S; Rashidi, A (2013)
According to the class of hypovolaemic shock, a blood loss less than 750 ml is not associated with the physiological changes. As a result it may cause a delay in fluid resuscitation. We postulate inferior vena cava (IVC) diameter reduction in inspiration and expiration may resemble the significant volume of blood loss in a healthy adult. We conducted a study to examine the changes of the IVC diameter pre and post blood donation.The inferior vena cava diameter during inspiration (IVCi) and expiration (IVCe) were measured using ultrasound (GE HEALTH) in supine position before and after blood donation of 450 ml. Paired t-test and Wilcoxin rank test were used to analyse the data. Forty two blood donors enrolled during the study period. The mean age of blood donors was 32.3 +/- 8.9 and mainly male blood donors. The mean IVCe of pre and post blood donation was 18.5 +/- 6.2 mm (95%CI 18.23, 18.74) and 16.6 +/- 6.6 mm (95%CI 16.35, 16.76) respectively. Meanwhile, the mean IVCi of pre and post blood donation was 17.1 +/- 8.6 mm (95%CI 16.89,17.30) and 15.6 +/- 6.6 mm (95%CI 15.43,15.81) respectively. The mean difference of IVCe pre and post blood donation was 1.9 +/- 0.5 mm (95%CI 1.75, 2.13) (p<0.001). In contrast, the mean difference of IVCi pre and post blood donation was 1.5 +/- 0.5 mm (95%CI 1.34, 1.68) (p<0.001). As a conclusion, the measurement of IVC diameter by ultrasound can predict the volume of blood loss in simulated type 1 hypovolaemia patient.